Commercially Available Preparations of Recombinant Wnt3a Contain Non‐Wnt Related Activities Which May Activate TGF‐β Signaling. Issue 4 (22nd September 2015) - Carthy, Jon M.; Engström, Ulla; Heldin, Carl‐Henrik; Moustakas, Aristidis
ABSTRACT: The Wnt ligands are a family of secreted signaling proteins which play key roles in a number of cellular processes under physiological and pathological conditions. Wnts bind to their membrane receptors and initiate a signaling cascade which leads to the nuclear localization and transcriptional activity of β‐catenin. The development of purified recombinant Wnt ligands has greatly aided in our understanding of Wnt signaling and its functions in development and disease. In the current study, we identified non‐Wnt related signaling activities which were present in commercially available preparations of recombinant Wnt3a. Specifically, we found that treatment of cultured fibroblasts with recombinant Wnt3a induced immediate activation of TGF‐β and BMP signaling and this activity appeared to be independent of the Wnt ligand itself. Therefore, while purified recombinant Wnt ligands continue to be a useful tool for studying this signaling pathway, one must exercise a degree of caution when analyzing the results of experiments that utilize purified recombinant Wnt ligands. J. Cell. Biochem. 117: 938–945, 2016. © 2015 Wiley Periodicals, Inc.